ANALISIS FAKTOR-FAKTOR YANG MEMENGARUHI KORUPSI DI KAWASAN ASIA PASIFIK - Happy Febrina Hariyani; Dominicus Savio Priyarsono; Alla Asmara (JURNAL EKONOMI DAN KEBIJAKAN PEMBANGUNAN, 2016)
The phenomenon of corruption is a big problem faced by countries with rapid economic development. The problem is not only faced by developing countries, but also in some developed countries. The factors that cause corruption classified into three broad categories--economic, political and socio-cultural. The high level of corruption in a country can also cause high cost economy that could hamper economic growth through the obstacles that occur in the investment. The purpose of this study is to analyze the factors that affect the level of corruption and to analyze the impact of corruption on economic growth in the Asia Pacific region. The results show that public budget, political stability, and urban population affect the level of corruption. Low institutional quality, indicated by the failure of the government (corruption), has a bad influence on economic growth performance.